The Influence of Big Five Personality Traits and Gender on College Student Subjective Well-Being - -, Adinda (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Students face various demands during their education, which can lead to low college student subjective well-being. College student subjective well-being is a person's evaluation of their life, specifically the extent to which their meaningful assessments and affective reactions indicate that their life is desirable and going well. Several factors influence college student subjective well-being, including Big Five personality traits and gender. This study aimed to determine the influence of Big Five personality traits and gender on college student subjective well-being. Data collection methods used demographic data, gender, the College Student Subjective Well-Being Questionnaire, and the Big Five Personality Questionnaire IPIP BMF-50. The subjects were 228 students from the fourth to eighth semesters of Malahayati University, Bandar Lampung. Statistical tests revealed that Big Five personality traits and gender simultaneously influenced college student subjective well-being. Other findings indicate that gender and the personality trait of conscientiousness are the strongest predictors of college student subjective well-being, while neuroticism has no effect on college student subjective well-being. The implications of this research can be used as input for students to actively engage, improve motivation, concentration, and academic performance, and influence student-faculty relationships, potentially fostering more positive interactions and academic support.